2016
DOI: 10.3390/computation4030037
|View full text |Cite
|
Sign up to set email alerts
|

Computational Streetscapes

Abstract: Abstract:Streetscapes have presented a long-standing interest in many fields. Recently, there has been a resurgence of attention on streetscape issues, catalyzed in large part by computing. Because of computing, there is more understanding, vistas, data, and analysis of and on streetscape phenomena than ever before. This diversity of lenses trained on streetscapes permits us to address long-standing questions, such as how people use information while mobile, how interactions with people and things occur on str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 385 publications
(481 reference statements)
0
10
0
Order By: Relevance
“…There are natural affinities between typology-type approaches to customer journeys and agent-based modeling, where significant work already presents on classes and ontologies of agent characteristics and agent behaviors relative to urban processes and phenomena (Benenson and Torrens 2004 ), often at street-level (Torrens 2016a ). Batty et al ( 2003 ) discussed how the categorization of pedestrians must necessarily shift as the scale of observation of their behavior shifts.…”
Section: Using Agents To Model the Customer Journey On High Streetsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are natural affinities between typology-type approaches to customer journeys and agent-based modeling, where significant work already presents on classes and ontologies of agent characteristics and agent behaviors relative to urban processes and phenomena (Benenson and Torrens 2004 ), often at street-level (Torrens 2016a ). Batty et al ( 2003 ) discussed how the categorization of pedestrians must necessarily shift as the scale of observation of their behavior shifts.…”
Section: Using Agents To Model the Customer Journey On High Streetsmentioning
confidence: 99%
“…Millonig and Gartner ( 2011 ) articulated this point well in their examination of wayfinding behavior among shoppers: “For pedestrians, the shortest path does not always represent the optimal route for an individual’s purposes, as studies have revealed that people often forgo to take the shortest path and prefer the ‘most beautiful’, ‘most convenient’ or ‘safest’ path.” (p. 3). Moreover, pedestrians have many degrees of freedom in their movement through urban streetscapes and their paths may often become highly dynamic, reactive, and adaptive, bucking the simple drivers that computational heuristics may suggest as proxies for their planning behavior (Torrens 2016a ).…”
Section: Using Agents To Model the Customer Journey On High Streetsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the commercially available robots, the My Spoon Robot, can aid in eating for those who are unable to coordinate their dexterity (Bedaf et al 2015 ). Typically, ageing bodies have been approached at the level of physical bodies, and their relations to other bodies and things have been calculated using agent-based movement models to depict patterns of behaviour (Torrens 2016 ).…”
Section: Ageing Agency and Dignitymentioning
confidence: 99%
“…While plenty of ABMs for pedestrian movement in indoor contexts have been advanced [see: [121][122][123], models dealing with large number of people in urban contexts are rarer [35,36,82]. In this context, our model is specifically intended to understand pedestrian dynamics at the urban scale.…”
Section: Plos Onementioning
confidence: 99%